(untitled) (Journal of actual problems of jurisprudence, 2018)
The laws on combating extremism and terrorism specify the importance of mutual cooperation of the law-enforcement and special state authorities of the Republic of Kazakhstan on combating extremism and terrorism. Statistical data obtained from the official sources show that the country has the threat of extremism and terrorism, as well as tendency of its development. The proposal on mutual cooperation was made, where arrangement of investigation of crime related to extremism by establishment of the inter-departmental investigation and operational group on investigation of the crime related to extremism and acts of terrorism is considered as effective. Conduction of investigation and operational actions in the investigation and operational group provides the possibility to apply all knowledge and skills at the same time and open abilities of employees of various law-enforcement authorities. The opportunity of rapid and maximum effective conduction of investigation and operational actions is described. The laws regulating mutual cooperation between the law-enforcement and special state authorities are specified. Key words: extremism, terrorism, law-enforcement authorities, authorities of internal affairs, national security authorities, inter-departmental investigation and operational group.